Literacy and virtual learning in the new normal: implications for quality educational access in Nigeria (2023)
This paper aims at explaining the concepts that have been added to literacy literature given the change that was brought about by the use of virtual learning. Even when the borders and management of the classroom setting have been expanded by the virtual reality, learners and instructors at all levels still have to be conscious of the guides to learning on the basis of human centredness. Literacy can be conceptualised as skills, attitude and competencies in individuals and groups of people as they relate with others in the community. The issues that are discussed are the reality of new normal and its implications for virtual learning. This discussion was done with the hindsight of what literacy was before the emergence of the new normal and virtual learning. Since curriculum development and policy formulation for implementation in learning situations may not meet up with the high demands of the virtual learning in the new normal, the paper suggests that there is need to strengthen the non - formal strategies for supporting learning in educational system. That is, in between the rigid formal system and overtly loose virtual learning there should be some sort of regulation.